Implementasi Design Thinking Dalam Product Management Untuk Menciptakan Layanan Fintech “Paymily” - Dhiya Ul Hikmah; R. Yuniardi Rusdianto (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
Fintech, or financial technology, is one of Indonesia's sectors with the quickest rate of growth.. This growth is driven by the increasing demand for people for fast, easy, and affordable financial services. One of the most popular fintech products is the e-wallet. In creating a successful e-wallet product, It's critical to comprehend user requirements and preferences. Design thinking is a user-centered approach to product development. This method can help product management teams to understand user needs, define the problem they want to solve, and generate innovative and user-centered solutions.